2019
DOI: 10.1093/cdn/nzz057
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cystatin SN Binds to Phytic Acid In Vitro and Is a Predictor of Nonheme Iron Bioavailability with Phytic Acid Supplementation in a Proof of Concept Pilot Study

Abstract: Background Acute phytic acid intake has been found to decrease iron bioavailability; however, repeated phytic acid consumption leads to iron absorption adaptation. Salivary proline-rich proteins (PRPs) have been shown to inhibit iron chelation to tannins and may mediate similar iron absorption adaptation with phytic acid intake. Objectives The objectives of this study were to determine whether salivary proteins bind to phytic acid in vitro, and to explore a proof of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In this study, food pattern modeling was used to predict hematological indices for four variables: iron, ascorbic acid, phytate, and phytate–iron ratios. These variables were chosen due to their known impact on the hematological indices of iron status and to their common focus in community nutrition research and programming [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, food pattern modeling was used to predict hematological indices for four variables: iron, ascorbic acid, phytate, and phytate–iron ratios. These variables were chosen due to their known impact on the hematological indices of iron status and to their common focus in community nutrition research and programming [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 , 21 , 22 , 23 , 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, while food pattern modeling may be non-inferior to 24 h dietary recall methods for long-term markers of iron status, it may be inadequate to predict acute markers of iron absorption. However, it has been suggested that dietary iron intake may be poorly predicted by single-meal iron bioavailability studies compared to long-term markers or iron status [ 3 , 12 , 13 , 33 ], questioning whether the improved diagnostic capabilities of 24 h dietary recalls may be needed in community-based dietary assessment. In addition, the mean difference in diagnostic accuracy for all nutrient variables for any hematological outcome between assessment methods was less than twenty percent, often trending in favor of food pattern modeling methods for assessment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations